PENGARUH PELATIHAN, PENGALAMAN MENGAJAR DAN KOMPENSASI TERHADAP PROFESIONALISME GURU DI SMK NEGERI 3 PALU - Rahmawati, Sri (Katalogis, 2015)
This study aims to explore and analyze simultaneous and partial influence of training, teaching experience and compensation on teachers’ professionalism in SMK Negeri 3 Palu. Also, this study intends to analyze professionalism differences among teachers who in charge for normative, adaptive and productive subjects in SMK Negeri 3 Palu. Type of the research is explanative and it uses census-sampling method with multiple linear regressions analysis. The result indicates that training, teaching experience and compensation simultaneously and partially influence teachers’ professionalism in SMK Negeri 3 Palu. Also, there are no differences on professionalism among teachers who teach normative, adaptive and productive subjects in SMK Negeri 3 Palu.